2021
DOI: 10.1016/j.omtn.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Engineering highly efficient backsplicing and translation of synthetic circRNAs

Abstract: Circular RNAs (circRNAs) are highly stable RNA molecules that are attractive templates for expression of therapeutic proteins and non-coding RNAs. In eukaryotes, circRNAs are primarily generated by the spliceosome through backsplicing. Here, we interrogate different molecular elements including intron type and length, Alu repeats, internal ribosome entry sites (IRESs), and exon length essential for circRNA formation and exploit this information to engineer robust backsplicing and circRNA expression. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 34 publications
(51 reference statements)
1
31
0
Order By: Relevance
“…There is also evidence that circRNAs can encode proteins and regulate translation by serving as sponges for miRNAs and RNA-binding proteins [112][113][114] . Methods for synthesizing engineered circRNA devices in cells have been described that use various mechanisms, including ribozyme cleavage and tRNA ligation, group I self-splicing introns and backsplicing [115][116][117] . Each of these methods was demonstrated to create synthetic circRNAs that can be translated to proteins in cells.…”
Section: Circular Rnas As Temporally Stable Translation Platforms and Molecular Spongesmentioning
confidence: 99%
“…There is also evidence that circRNAs can encode proteins and regulate translation by serving as sponges for miRNAs and RNA-binding proteins [112][113][114] . Methods for synthesizing engineered circRNA devices in cells have been described that use various mechanisms, including ribozyme cleavage and tRNA ligation, group I self-splicing introns and backsplicing [115][116][117] . Each of these methods was demonstrated to create synthetic circRNAs that can be translated to proteins in cells.…”
Section: Circular Rnas As Temporally Stable Translation Platforms and Molecular Spongesmentioning
confidence: 99%
“…This method realized RNA ligation through a regular group I intron self-splicing reaction, including two transesterifications at defined splice sites ( Figure 4A ). PIE method can be used for RNA cyclization in vitro and in vivo ( Meganck et al, 2021 ), which broadens its application. Compared to chemical ligation and enzymatic ligation, PIE method could be applied for the cyclization of larger linear RNA precursor, and the reaction condition and purification method of PIE method is simpler.…”
Section: Synthesis Of Circrnas In Vitromentioning
confidence: 99%
“…In the splicing reporter assay, the inclusion or exclusion of an exon results in the in-frame expression of the reporter gene, allowing for the identification of compounds that regulate the splicing process ( Figure 1 A(iii)). A reporter system was recently used to identify molecular elements critical for back-splicing [ 46 ], which may be repurposed to screen for small molecules that promote circRNA expression. Additionally, with the knowledge of the regulatory sequences of ncRNAs, the putative transcription factors that regulate the ncRNAs can be predicted.…”
Section: Discovery and Validation Of Small Molecules Targeting Ncrnasmentioning
confidence: 99%
“…Two separate studies also found a downregulation of circHOMER1 and circKCNN2 and an upregulation of circDOCK1 in AD frontal and parietal cortices [ 127 , 131 ]. To identify small molecules that modulate the back-splicing, and hence biogenesis, of circRNAs, the splice sites of these RNAs can be cloned into a plasmid in which the successful back-splicing and circularization of the RNA results in the in-frame expression of a reporter [ 46 ]. As such, small molecules that modulate the reporter intensity may also be able to modulate circRNA expression.…”
Section: Examples Of Adrd-relevant Ncrnas and Screening Strategiesmentioning
confidence: 99%